The Higaonons of Rogongon Their Traditional Beliefs and Cultural Practices - Tangian, Ma. Cecilia B. (2010)
The Higaonons of Mindanao belong to the original stock of proto-Philippine They are one the or proto-Austronesian. They came from South China thousands of years ago, the than the Ifugao and other terrace-building people of Luzon," least known ethno-linguistic groups that inhabit Northern and Central Mindaan, is the mountainous sections of Misamis Oriental, the highlands of Bukidnon, in the foothills of Agusan, and in the mountain ranges of Eastern and Western Lanso Lanao del Norte, the Higaonons are found in Rogongon, one of the 44 barangays located at the northeastern part of Iligan City. Rogongon has a land area of 32,000 hectares, It became a barangay through Republic Act 2370 of 1962 Rogongon is characterized by the vast rolling hills, continued mountain ranges and its plateau at the poblacion itself.

Rogongon is a community of varied cultures, a melting pot of tri-people in Mindanao: the Higanonons, the Christian migrants and the Kolibugan (muslim culture). This tribe applied for a Certificate of Ancestral Domain Title (CADT) to protect the legality of their land, although it was not yet been awarded to them. The inhabitants are an advocate of peace process in Northern Mindanao as shown in their harmonious relationship despite their varied cultural backgrounds. The Higaonon term came from higa, which, in the binukid dialect, means settlement, and non, which means highland people.
Keywords: Higaonon (Philippine people); Traditional knowledge